Assessing Urban Park Accessibility and Equity Using Open-Source Data in Jiujiang, China - Lihui Gao; Zhen Xu; Ziqi Shang; Mingyu Li; Jianhui Wang (Land)
Urban parks have become more important in residents’ daily lives owing to both rapid urbanization and increasing environmental pressures. Globally, there is growing concern regarding equitable access to urban parks, particularly in densely populated countries such as China. This study focuses on the accessibility and equity of urban parks in Jiujiang using walking route data obtained from an open-source platform through an application programming interface to assess park accessibility. We explored the equity of park accessibility from three perspectives: spatial, opportunity, and group equity. The results indicated that urban parks in central Jiujiang have significantly better accessibility than those in suburban areas. Less than half of the study area was covered within a 1500 m walking distance. There is a large service blind catchment in park accessibility. Similarly, disparities in the equity of park accessibility were observed. The Penpu sub-district has the best accessibility; in contrast, the Qili Lake sub-district benefits from less than 10% of park accessibility. Wealthier communities benefit more from park accessibility than disadvantaged communities. Our study aims to provide strategies for urban planning for policymakers. Strategies such as increasing park entrances, opening gated communities, and creating shared green spaces may help ensure environmental equity.